Taking turns : stories from HIV/AIDS care Unit 371 - Czerwiec, MK (MaryKay), 1967- (Graphic medicine., 2017)
"A graphic memoir and adapted oral history of Unit 371, an inpatient AIDS care hospital unit in Chicago that was in existence from 1985 to 2000. Examines the human costs of caregiving and the role art can play in the grieving process"--Provided by publisher